Pendapatan Usahatani Seledri (Apium Graviolens L) di Desa Pancasari Kecamatan Sukasada Kabupaten Buleleng - NI MADE VONAMM DELON SUPANTA PANDE; RATNA KOMALA DEWI; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
Income of Celery Farming (Apium Graviolens L) in Pancasari Village, Sukasada District, Buleleng Regency Celery cultivation is best applied at high altitudes at an altitude of 700 - 1500 masl. One of the areas that have become the centers of celery farming in Bali is Pancasari Village in Sukasada Subdistrict, Buleleng Regency. However, farmers in the village are still facing some problems including insufficient knowledge on farming and farm feasibility analysis, as well as limited funding. Farmers may make inaccurate calculations so that farming becomes inefficient. Fluctuation in selling price subsequently affects their income. This study aims to determine the income and efficiency of celery farming. The study was conducted in Pancasari Village, involving 33 celery farmers as respondents during the planting season between February and August in 2018. The study suggests the income of celery farmers with 0.04 hectares of arable land is Rp 1,220,460.34. The efficiency of celery farming is efficient with an R/C ratio of 1.88.